Geophysical and geochemical investigations of underwater sulphurous seeps from Western Black Sea (Mangalia area, Romania), in support of habitat conservation - Popa, Adrian; Stanciu, Irina Marilena; Drăguşin, Virgil; Teacă, Adrian; Balan, Sorin Vasile; Popa, Mihai Emilian; Ion, Gabriel; Ispas, Bogdan-Adrian (Frontiers in Marine Science, 2024)
Mangalia area harbors in the western Black Sea a distinctive marine environment thriving under specific hydrochemical conditions, largely influenced by a significant number of sulphurous springs occurring in shallow marine waters. These springs led to the designation of the area as part of the Natura 2000 Marine Protected Area (MPA) network at European level (Underwater Sulphurous Springs from Mangalia -ROSAC0094), as unique hydro-geomorphological features in the region. In 2021 and 2023, two research cruises led by GeoEcoMar investigated underwater sulphurous springs primarily located offshore of Mangalia (Constanța County, Romania). The study area, located between 17-29 meters water depth and 1.8-3 km offshore, encompasses two marine protected areas: the Underwater Sulphurous Springs from Mangalia (ROSAC0094) and Cape Aurora (ROSCI0281). The research combined geophysical and geochemical techniques and sediment sampling. Considering the susceptibility of these natural systems to human activities such as fishing and dredging, as well as the impact of ecological and climate changes, this paper offers significant insights contributing to the development of effective conservation and management strategies for these environments. The surveys were conducted for benthic habitats mapping, with the objective of improving our understanding of these ecosystems' distribution, composition and dynamics. As these sulphurous waters are rich in methane, a powerful greenhouse gas, our results also contribute to the inventory of greenhouse gas sources. The results presented in this paper provide valuable new insights into this specific environment, contributing to the understanding of its complex functioning and evolution.